Impact of disclosure of a dementia diagnosis on uptake of support services: A pilot study exploring a post-traumatic stress approach. (November 2020) - Dunham, Annette; Mellor, David; Rand, Elizabeth; McCabe, Marita; Lewis, Matthew
Background: At time of diagnosis, people with dementia and their carers can access support services to help them to plan for their future care needs, but often they do not engage with these services. It is not clear why this occurs but a potential explanation explored in this paper is that disclosure of a dementia diagnosis is an overwhelming and highly stressful event that may lead to behavioural avoidance in the manner of post-traumatic stress. In this study we use a post-traumatic stress screening tool to determine whether being diagnosed with dementia shares some qualitative similarities with post-traumatic stress disorder and explore whether this is associated with a reduced likelihood to engage support services following diagnosis. Method: We conducted a small pilot study through the local memory clinic with eight people with dementia and 11 carers returning surveys. Participants completed the Impact of Events Scale-Revised, a validated post-traumatic stress disorder screening tool, and also provided information regarding their experience of the diagnosis and subsequent use of support services. Results: One person with dementia and two carers had scores on the Impact of Events Scale-Revised indicating a probable diagnosis of post-traumatic stress disorder and two people with dementia and two carers scored within the range of clinical concern. The average Impact of Events Scale-Revised score of those who had taken-up a referral to home support was significantly lower than those who had not. Conclusion: A dementia diagnosis can be associated with symptoms that are consistent with post-traumatic stress, which in turn may affect engagement with support services.